1997
DOI: 10.1111/j.2044-8279.1997.tb01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Student teacher anxieties related to class management, pedagogy, evaluation, and staff relations

Abstract: Student-teacher anxieties are related to demographic variables, experiential variables, and dispositional variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
17

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 14 publications
2
67
0
17
Order By: Relevance
“…As análises realizadas, tomando estas duas variáveis, procuram averiguar em que medida os dados encontrados na literatura (e.g., Admiraal et al, 2000;Head et al, 1996;Morton et al, 1997) encontram reflexo na presente amostra, ou seja, se o género e a área de formação dos sujeitos exercem influência sobre as suas vivências e percepções do estágio. No Quadro 1 dão-se, também, a conhecer os valores obtidos na amostra global.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…As análises realizadas, tomando estas duas variáveis, procuram averiguar em que medida os dados encontrados na literatura (e.g., Admiraal et al, 2000;Head et al, 1996;Morton et al, 1997) encontram reflexo na presente amostra, ou seja, se o género e a área de formação dos sujeitos exercem influência sobre as suas vivências e percepções do estágio. No Quadro 1 dão-se, também, a conhecer os valores obtidos na amostra global.…”
Section: Resultsunclassified
“…Apesar de algumas das diferenças observadas no repertório de vivências e percepções destes estagiários consoante a sua pertença aos subgrupos em análise, estas não encontram a expressão que alguma da literatura na área sugere (Admiraal et al, 2000;Head et al, 1996;Morton et al, 1997;Serow, 1998). A variabilidade encontrada na amostra em estudo parece ser melhor explicada pelas idiossincrasias associadas à fenomenologia do "Tornar-se professor", largamente condicionada pelas múltiplas sinergias criadas entre os espaços, os tempos e os actores que jogam neste processo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Other research has highlighted how certain factors intrinsic to the teaching profession can facilitate high levels of stress. For example, heavy workloads and long working hours (TRAVERS & COOPER 1996), overload of competing roles, inconsistent workloads over the academic year (KINNUNEN & LESKINEN 1989), the need for classroom management (LEWIS 1999;MORTON et al 1997), and evaluation apprehension (CAPEL 1997;MORTON et al 1997).…”
Section: The Energetic Processmentioning
confidence: 99%
“…In another gender-related issue, there has been some research that reported that females generally find the practicum experience more stressful than do males (D'Rozario & Wong, 1996;Morton, Vesco, Williams, & Awender, 1997); but that all practicum participants report a reduction in stress by virtue of experiencing the daily routines of teaching during the practicum (Murray-Harvey et al, 2000;Ralph, 2004b;Smith & Sanche, 1993).…”
Section: Gender Of Internsmentioning
confidence: 99%